PEMBERIAN GRASI TERHADAP TERPIDANA SEBAGAI HAK PREROGATIF PRESIDEN (Studi Atas Penggunaan Hak Grasi Presiden Terhadap Kasus-Kasus di Indonesia) - Dientia Dinnear (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Abstract Clemency is a gift by the President in the form of forgiveness in the form of change, mitigation, reduction, or elimination of the implementation of the decision to convict. Granting of pardon is the prerogative of the President togrant a pardon. Over time, the president's authority to grant clemency sometimes leads to controversy. Therefore, it appears the problem